Practical recommendations for the use of therapeutic drug monitoring of biopharmaceuticals in inflammatory diseases - Dreesen E; Bossuyt P; Mulleman D; Gils A; Pascual-Salcedo D (Dove Medical Press, 2017)
Erwin Dreesen,1 Peter Bossuyt,2,3 Denis Mulleman,4 Ann Gils,1 Dora Pascual-Salcedo5 1Laboratory for Therapeutic and Diagnostic Antibodies, Department of Pharmaceutical and Pharmacological Sciences, KU Leuven, Leuven, 2Imelda GI Clinical Research Centre, Imelda Ziekenhuis, Bonheiden, 3Translational Research in GastroIntestinal Disorders (TARGID), Department of Clinical and Experimental Medicine, KU Leuven, Leuven, Belgium; 4Department of Rheumatology, Université François-Rabelais de Tours, CNRS, UMR 7292, Tours, France; 5Institute for Research IdiPAZ, University Hospital La Paz, Madrid, Spain Abstract: Biopharmaceuticals directed against tumor necrosis factor-alpha, integrins, interleukins, interferons and their receptors have become key agents for the management of inflammatory diseases in the fields of gastroenterology, rheumatology, dermatology and neurology. However, response to these treatments is far from optimal. Therapeutic failure has been attributed in part to inadequate serum concentrations of the drug and the formation of antidrug antibodies (ADA). Therapeutic drug monitoring (TDM) based on drug concentrations and ADA represents a pharmacologically sound tool for guiding dosage adjustments to optimize exposure. Although becoming standard practice in tertiary care centers, the widespread accessibility and recognition of TDM is hindered by several hurdles, including a lack of education of health care providers on TDM. In this paper, the Monitoring of monoclonal Antibodies Group in Europe (MAGE) provides an introduction on the fundamental principles of the concept of TDM, aiming to educate clinicians and assist them in the process of implementing TDM of anti-inflammatory biopharmaceuticals. Keywords: therapeutic drug monitoring, biopharmaceuticals, trough concentration, immunogenicity, antidrug antibodies, inflammatory diseases